The Impacts of Home Visits on Students in Learning English during the Pandemic - Andi Nur Hasanah; Kurnia Kurnia; Shafwan Nugraha (Edumaspul: Jurnal Pendidikan, 2021)
The government has taken policy by circular letter number 4 2020 about the implementation of educational policies in the emergency period of the Covid-19. It means all of the learning processes are conducted from home or it called distance learning (PJJ). Unfortunately, not all school can implement online learning due to internet connection limitation. SMP Negeri 3 Totikum, Banggai Kepulauan is one of an example. The school that did not have an internet connection conducted the learning process by distributing modules and apply self-study to all the students. This causes the learning motivation of students were decrease. In learning activities, motivation is needed to improve students' enthusiasm for learning so that learning activities can run well. This research aims to highlightthe impact of home visits on students’ motivation of the Eighth Grade of SMP Negeri 3 Totikum in learning English during Pandemic Covid-19. This research method used qualitative approach. The data collection was processed by questionnaire. The result show that almost students the Eighth grade of SMP Negeri 3 Totikum were strongly and agree with that statements that shows the indicators of motivation. In conclusion,home visit can give impact on students’ motivation in learning English, specially in the school or area that did not have an internet connection